Life cycle and metrics to measure the resilience of business processes by considering resources. Issue 4 (15th August 2022) - Stocker, Joachim; Herda, Nils; Jürjens, Jan
Abstract : Purpose: Enterprises often face a wide variety of adverse events. Adverse events can have negative effects on organizations like failures of resources. In case resources fail, they are not available and cannot perform the assigned work. Enterprises are therefore especially interested in how resilient processes and workflows are in case adverse events occur and resources may fail. For this purpose, process resilience measurement approaches are needed. Design/methodology/approach: To measure the resilience of processes and workflows, a life cycle and five quantitative metrics have been developed. The metrics have been validated using five real-world production and logistics cases to show their applicability on process models and paths. Furthermore, workshops have been conducted with professionals to get additional feedback on the contributions. Findings: Based on the results obtained from applying the metrics to five real-world cases, view-based resilience improvements can be derived. Overall, only one of the five real-world cases can be considered as completely resilient. Furthermore, the metrics and life cycle have been especially valued by professionals with respect to transparency, independency, comparability as well as the ability to determine critical process paths. Originality/value: Several authors have dealt with different aspects related to the measurement of business processes, resilience or a combination thereof. However, a life cycle or metrics to quantitatively measure the resilience of processes by considering resources has not been found yet. The life cycle and metrics are therefore novel. As a future research direction, they can be applied in different domains for further validation purposes.